Pengaruh Work-Life Balance Dan Job Satisfaction Terhadap Turnover Intention Pada Karyawan - Zainul Arifin; Anggella Marshanda Putri (Universitas Galuh, 2026)
Human Resource Management (HRM) as a division responsible for managing an organization's human resources plays an important role in determining whether an organization succeeds or not. One of the biggest challenges companies face in managing HR is turnover intention, or employees' intention to resign, because it not only increases recruitment and training costs but also lowers the company's image and stability. This study aims to analyze the effect of work-life balance and job satisfaction on turnover intention. The research was conducted using a quantitative approach with SEM-PLS via SmartPLS 4.0, and the sampling technique used was a census, meaning the entire population, which in this case is all employees of BAYIKU.ID, totaling 37 people. The research results show that work-life balance has a positive but not significant effect on turnover intention. This is suspected to be because turnover intention is more influenced by other dominant factors like compensation, leadership, and job satisfaction, so it's not the main factor affecting employees' decisions to stay. On the other hand, job satisfaction has a negative and significant effect on turnover intention. This means that the higher the level of job satisfaction, the lower the employees' desire to resign. This study contributes to understanding employee retention in a startup environment.